EFEKTIVITAS KOMBINASI KEPALA UDANG, GAPLEK DAN MINYAK KELAPA SEBAGAI PENGGANTI SEBAGIAN JAGUNG TEPUNG TERHADAP PERFORMANS ITIK MOJOSARI JANTAN - Devi Anthonia Juliana Ndolu; Johanis A Jermias (Partner, 2020)
The study was aimed to determine the effect of partially substitute corn with cassava flour, shrimp heads, and coconut oil on the performance of male Mojosari ducks. The 96 male daily old ducks were given treatment feed which was a combination of cassava flour, shrimp head, and coconut oil as corn substitutes with stratified proportions of 0, 5, 10, and 15. This was an experiment arranged according to a randomized block design with 4 treatments and 6 repetitions. The results showed that the combination of shrimp head, cassava, and coconut oil as corn to 15 percent has no difference in effect (P> 0.05) on feed consumption, metabolic energy consumption and protein consumption, carcass weight, thigh weight, and breast weight of duck age 6 Sunday. The conclusion is that the combination of shrimp heads, cassava, and coconut oil up to 15% could not affect the performance of male Mojosari duck.